A multi-criteria decision making approach to balance water supply-demand strategies in water supply systems - Géssica Maria Cambrainha; Marcele Elisa Fontana (Production)
Abstract Paper aims this paper proposes a model to aid a group of decision makers to establish a portfolio of feasible actions (alternatives) that are able to balance water supply-demand strategies. Originality Long periods of water shortages cause problems in semi-arid region of northeast Brazil, which affects different sectors such as food, public health, among others. This problem situation is intensified by population growth. Therefore, this type of decision making is complex, and it needs to be solving by a structured model. Research method The model is based on a problem structuring method (PSM) and a multi-criteria decision making (MCDM) method. Main findings Due to society and government influences, the proposed model showed appropriate to conduct a robust and well-structured decision making. Implications for theory and practice The main contributions were the study in regions suffering from drought and water scarcity, as well as the combination of PSM and MCDM methods to aid in this problem.